2022
DOI: 10.34172/ijhpm.2022.7297
|View full text |Cite
|
Sign up to set email alerts
|

Beyond "Lack of Political Will": Elaborating Political Economy Concepts to Advance "Thinking and Working Politically" Comment on "Health Coverage and Financial Protection in Uganda: A Political Economy Perspective"

Abstract: Political economy analysis (PEA) has been advanced as critical to understanding the political dimensions of policy change processes. However, PE is not a theory on its own but draws on several concepts. Nannini et al., in concert with other scholars, emphasise that politics is characterised by conflict, contestation and negotiation over interests, ideas and power as various agents attempt to influence their context. This commentary reflects how Nannini et al. wrestled with these PEA concepts- summarised in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…This reflects a strategy often used in countries to navigate donor influences called ‘shadow diplomacy,’ where ‘informal networks and channels of influence run parallel to, but are not recognised as part of formal diplomacy’ [ 29 ]. This scenario also underscores a trend where global actors (donors) are increasingly interested in working with local CSOs and are in tandem increasing their financial support to these organisations [ 31 ]. The close collaboration between CSOs and global actors has led to a development where the latter leverage CSOs to advance their interests [ 27 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reflects a strategy often used in countries to navigate donor influences called ‘shadow diplomacy,’ where ‘informal networks and channels of influence run parallel to, but are not recognised as part of formal diplomacy’ [ 29 ]. This scenario also underscores a trend where global actors (donors) are increasingly interested in working with local CSOs and are in tandem increasing their financial support to these organisations [ 31 ]. The close collaboration between CSOs and global actors has led to a development where the latter leverage CSOs to advance their interests [ 27 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…One review indicated examples of where global health initiatives leverage their financial and technical affluence to determine country priorities [ 32 ]. Although the GFF undeniably bore the stamp of being ‘government-led’ and indeed used established government structures, this may not equate to truly representing local RMNCAH priorities [ 31 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PEA methodology is a structured qualitative approach examining power dynamics and economic and social forces influencing development. [23][24][25][26] The analytical approach in this study is informed by the applied political economy, which has three primary constructs: (1) problem identification, which examines the operational or developmental problem to be addressed by looking at the relationships between individuals, communities and Institutions, their motivations which are either personal, cultural, political, financial; (2a) Structural diagnosis which looks at the contextual and institutional characteristics relevant to the problem. The context examines the analysis of relevant structural features such as culture and social structures, demography, geopolitics and culture.…”
Section: Methodology Study Designmentioning
confidence: 99%
“…Secondly, the commentary proposes additional considerations and existing theories to avoid oversimplifications concerning the meaning of ideas, interests, and institutions. For instance, when referring to “institutions,” formal or informal rules shaping or impacting human action 16 should be considered.…”
mentioning
confidence: 99%